Role of circadian transcription factor REV-ERB in cardiovascular diseases: a review - Chunling Wang; Jiashu Yang; Jianfang Yuan; Xuyong Wang; Qianrong Li; Chunzhen Ren; Xiaodong Zhi; Xiaodong Zhi; Xinfang Lv; Kai Liu; Xinke Zhao; Yingdong Li (Frontiers in Cardiovascular Medicine)
Circadian rhythm, or the biological clock, is an intrinsic timing system present in organisms that operates on a cycle of approximately 24 h. Nearly every cell in the human body adheres to a specific circadian rhythm, governing various biological processes essential for overall health. REV-ERB, a key circadian clock-regulating gene, plays a crucial role in maintaining the precision of these rhythms. This gene influences many downstream targets associated with diverse pathophysiological processes, including metabolism, autophagy, immunity, inflammation, and aging across multiple organs. REV-ERB specifically impacts cardiac systolic function by regulating myocardial energy metabolism. In contemporary society, health and well-being are increasingly challenged by disruptions to the biological clock, such as night shifts, late-night activities, and jet lag. These disruptions often lead to circadian rhythm disorders, which are now being increasingly linked to heart diseases. This review explored the potential role of REV-ERB in the cardiovascular system. Beyond its role in circadian rhythm regulation, REV-ERB could significantly influence physiological and pathological processes related to cardiovascular health, including atherosclerosis, myocardial ischemia/reperfusion injury, and heart failure. Mechanistically, REV-ERB could regulate glucose and lipid metabolism, inflammation, autophagy, ferroptosis, and mitochondrial function. The review highlighted the protective roles and underlying mechanisms of REV-ERB in cardiovascular diseases, suggesting that multidisciplinary research may provide a basis for breakthroughs in REV-ERB-targeted therapies for cardiovascular disorders.